Replace Vista's clunky recent items list. - Spector, Lincoln
Flexigensoft's free ActualDoc, a powerful tool that provides separate recent lists for documents, pictures, and other file types, introduces a few simple user-defined parameters to solve the disappearing-files problem.
Keywords: Flexigensoft?ActualDoc.